Profissionalização de adolescentes e jovens em cumprimento de medida socioeducativa de internação na Paraíba : implementação no contexto da Fundac-2012/2022 - Barros, Waldir Victor de (2024)
The objective of this study is to analyze the implementation of Law No. 12,594/12, which legally constitutes the National Socio-Educational Assistance System (Sinase), with regard to the professionalization of adolescents and young people serving socio-educational measures of internment, in the context of the Child and Adolescent Foundation - Paraíba (Fundac-PB), in the period 2012-2022. Regarding the methodology, we worked with the techniques of documentary analysis and thematic content analysis of the documents that configure the implementation of the public policy at Fundac-PB, as well as of documents that generate the referred public policy: the Brazilian Constitution of 1988 and Law No. 12,594/12, in line with the principles listed in Law No. 8,069, of July 13, 1990 (Child and Adolescent Statute). The results and discussion were presented based on three documentary references: 1) the 1988 Brazilian Constitution and the articles that address issues related to the professionalization of adolescents and young people serving socio-educational internment measures; 2) Law No. 12,594/12; and 3) Fundac-PB: documents implementing Law No. 12,594/12, which refers to the professionalization of adolescents and young people serving socio-educational internment measures from 2012 to 2022. The purpose is to characterize the institutional actions developed to strengthen professionalization in socio-education. In the first documentary reference, the following thematic axes were identified: professionalization for work as a right; professionalization process to facilitate access to the job market; guaranteeing absolute priority to adolescents and young people with repercussions for professionalization. In the second documentary reference, the following thematic axes were highlighted: professionalization and qualification for work as rights; protection of adolescent work; professionalization and inclusion in work, so as not to lose their educational character. In the third batch of documentary references, documents produced by Fundac-PB, the themes that the management has presented in the process of implementing the aforementioned policy were identified: Fundac-PB - structure, processes and public policies for socio-education and professionalization; Fundac - Institutional Development Plan and professionalization in socio-education; Fundac - courses, internships, partnerships, training and learning. As for the intervention proposals, educational methodologies were suggested that promote the advancement of professionalization. The objective is the human emancipation of adolescents and young people in conflict with the law, by strengthening the pedagogical process that encompasses education in a comprehensive manner, as well as the periodic updating of the Institutional Political-Pedagogical Project (PPPI). The implementation of the public policy of professionalization is the law put into action, through which adolescents and young people in conflict with the law begin to have access to opportunities more consistent with the resocialization process. The research identified some weaknesses in the implementation of public policy, within the scope of Fundac, related the weaknesses identified with other studies that addressed the same issue and proposed axes capable of contributing to the management of the implementation of public policy in the context of Fundac, taking into account the reality in which the institution finds itself.